2008
DOI: 10.1080/15578770801943877
|View full text |Cite
|
Sign up to set email alerts
|

Does Prior Project Management Work Experience Have an Effect on the Academic Achievement of University Students in the Classroom?

Abstract: This study compared the academic achievement of students who participated in a cooperative education program (co-op students) with that of students who did not participate (nonco-op students). The alternate hypothesis was that students who gained knowledge through co-op work experience would use that knowledge in subsequent coursework and thus would achieve a higher grade point average (GPA) than students who did not participate in the co-op program. Historical data were analyzed for students (N ¼ 460) who gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Kramer (2008) found that, amongst students with a GPA (USA) ranging from 2.50 to 3.49, those with WIL experience performed better than those without in courses related to project management. It is possible that succeeding in these courses depends on students' maturity, self-management, teamwork, and real-life applications which they had developed during placement.…”
Section: Ii) Academic Performance Improvementmentioning
confidence: 99%
“…Kramer (2008) found that, amongst students with a GPA (USA) ranging from 2.50 to 3.49, those with WIL experience performed better than those without in courses related to project management. It is possible that succeeding in these courses depends on students' maturity, self-management, teamwork, and real-life applications which they had developed during placement.…”
Section: Ii) Academic Performance Improvementmentioning
confidence: 99%
“…These might be mandatory for course credit or strongly encouraged, yet voluntary, during college. Students who enter co-op or internship programs have been shown to earn higher grades in associated coursework, indicating the value of this off-campus work [8].…”
Section: Introductionmentioning
confidence: 99%